Individual Values for Organizational Success - Andó, Ildikó (Competitio, 2009)
Douglas McGregor published Theory Y in 1960. The main element of this theory is integration of individual and organizational objectives. Today, near 50 years later, the integration of individual and organizational goals remians only theory in several business organizations. The author of this study conducted an online survey in 2008 in order to examine company cultures, values was harmonization between organizational-level and individual-level sets of values. Two multinational companies with 324 respondents took part in the research up to this time. This publication shows the findings of the survey and illustrates the importance of harmonization between organizational-level and individual-level values. Finally, it comes up with some ideas what leaders can do in order to harmonize the value hierarchies efficiently in their organizations.JEL classification: D21, L21, L25